EFEKTIVITAS PENDEKATAN ETNOMATEMATIKA MELALLUI PERMAINAN ENGKLEK TERHADAP KEMAMPUAN NUMERASI SISWA KELAS III SD INPRES KASSI-KASSI - Rahmadani; Rezki Arimi Putri; Putri Nurul Amalia; Muh.Haikal; Salwa Nurul Amalia Rahman Siduppa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low numeracy skills of third-grade students at SD Inpres Kassi-Kassi, which is characterized by difficulties in understanding numbers, basic operations, and applying mathematical concepts in everyday life. This study aims to determine the effectiveness of the ethnomathematics approach through the engklek game on the numeracy skills of third-grade students at SD Inpres Kassi-Kassi. This study employed a quantitative research method with a pre-experimental design in the form of one group pretest-posttest design. The subjects of this study were 24 third-grade students at SD Inpres Kassi-Kassi. Data were collected through numeracy skill tests consisting of pretest and posttest, then analyzed using paired sample t-test and N-Gain score. The results showed that the average pretest score was 52.08, while the average posttest score increased to 80.42. The N-Gain score of 0.59 was in the moderate category. The results of the paired sample t-test showed a significance value of 0.000 < 0.05, which means that there is a significant difference between numeracy skills before and after the application of the ethnomathematics approach through the engklek game. Thus, it can be concluded that the ethnomathematics approach through the engklek game is effective in improving the numeracy skills of third-grade students at SD Inpres Kassi-Kassi.